Profit efficiency of shariah banks in Indonesia and the determining factors: Using Stochastic Frontier Analysis Method - Sri Wahyuni; Pujiharto Pujiharto (Journal of Economics, Business, and Accountancy Ventura, 2016)
This study aims to measure the efficiency of profit and examine the factors that affect the efficiency of shariah banks profit in Indonesia such as the size of banks, risk financing, and capital adequacy. This study used the Shariah banks in Indonesia, during the period of 2010-2014. These shariah banks were selected as the sample Commercial shariah banks and Shariah Business Units. This study uses three stages of research. First, it measures the efficiency of profit using a parametric approach that is Stochastic Frontier Approach (SFA). Secondly, its uses regression profit efficiency scores with various determinants of profit efficiency. The third phase is testing the efficiency score during the global crisis (2008-2009) and after the global crisis period (2010-2014). It shows that in overall there occurred profit efficiency in the shariah banks in Indonesia as it was indicated by the score of profit efficiency that is less than one. The inefficiency occurred in both Shariah banks and shariah business units. Bank size has a positive impact on profit efficiency. The bigger the bank, the better profit efficiency is. It can be implied that this research provides the managers the clues that shariah banks should improve their profit efficiency management. For Bank Indonesia, they can use this evidence to design policies that can encourage profit efficiency in shariah banks.